Quality assessment of endotoxin contamination in consumables used for assisted reproductive technology - Hiroyuki Tomari; Emi Sugizaki; Shaimaa Ibrahim; Yuki Hashiguchi; Genki Koyama; Yasuo Nakamura; Mayu Nagata; Yumi Nagata; Yuji Haishima (PLoS ONE, 2026)
Commercially available disposable products such as cell culture utensils and catheters do not necessarily possess sufficient quality for in vitro fertilization (IVF), from the perspective of pyrogen contamination. We aimed to comprehensively analyze the pyrogen contamination status, including bacterial endotoxins, of the products used for IVF in assisted reproductive technology (ART) and improve their cleanliness using a new sterilization technology. Pyrogen contamination levels were evaluated using a direct human cell-based pyrogen test that is not affected by the recovery ratio, unlike bacterial endotoxin tests. Pyrogen inactivation tests were performed using low-temperature ozone/hydrogen peroxide gas treatment. The residual hydrogen peroxide was colorimetrically quantified, and the effectiveness of its removal by drying treatment was evaluated using germ cell viability as an indicator. Significant amounts of pyrogen, from 0.014 to 1.110 EU/product, were detected in seven of the twenty products. Pyrogen contamination levels were reduced below the detection limit by ozone/hydrogen peroxide gas sterilization. Hydrogen peroxide remained on the surface of the GPS dish but was reduced to a level that did not affect human sperm viability and embryo development after drying at 80°C for 24 h following sterilization. These products may carry a potential risk of reducing ART success rates, and pyrogen contamination levels may exceed the previously reported allowable level of 0.01–0.02 EU/mL in human IVF during actual use. Our study suggests that the manufacturing of products free from pyrogens and without adverse effects on germ cells is possible using ozone/hydrogen peroxide gas sterilization and subsequent drying technologies.